Reaction Characteristics of Blast Furnace Slag-Based Non-Cement Paste Using Alkali Accelerator and Red Mud - Park, Sungyu; Kim, Yunmi; Lee, Sangsoo (Asian Journal of Chemistry, 2014)
This study involved to examine the strength properties and reactions of non-cement paste that used the blast furnace slag from steel manufacturing and red mud, the by-products. It was found that KOH, NaOH and Ca(OH)2 stimulated the blast furnace slag particles and created the C-S-H (calcium silicate) hydrate, etc., resulting in the hardening of non-cement paste. The results of compressive strength test suggested that both KOH and NaOH exhibited a tendency that compressive strength decreased as the replacement rate of red mud increased. In addition, the test specimen added with Ca(OH)2 showed the increased strength proportionally to the replacement rate, but showed much lower strength compared to that of KOH and NaOH.